The role of final-state interaction in tensor polarization effects of the reaction γd→pnπ0; Scientific Reports; Vol. 13, iss. 1 - Gauzshteyn V. V. Vyacheslav Valerjevich; Fiks (Fix) A. I. Alexander Ivanovich; Vasilishin B. I. Bogdan Ivanovich; Darwish E. M.; Kuzin M. Ya. Matvey Yaroslavovich; Levchuk M. I.; Loginov A. Yu.; Nikolenko D. M. Dmitry Mitrofanovich; Rachek I, A. Igor Anatoljevich; Shestakov Yu. V. Yury Vladimirovich; Toporkov D. K. Dmitry Konstantinovich; Yurchenko A. V. Arseny Vladislavovich; et al. (2023, 2023)
Title screen